Perception of Problem Constraints - Taylor, Ronald N. (Management Science, 1975)
The problem solver's perception of elements in a problem-situation will influence the extent to which he recognizes a problem and the nature of the constraints he associates with the problem. Constraints represent the extent to which the problem is defined or specified and problem formulation takes place as constraints are adjusted. Through such mechanisms as psychological set and functional fixedness, the previous problem-solving experiences of an individual can shape the constraints he perceives for subsequent problems. His prior experiences can either facilitate (positive transfer) or inhibit (negative transfer) problem solving, depending in part on the structure of the problem. The constraints likely to be associated with the problems of varying degrees of structure are examined and suggestions are made for reformulating problems by adjusting these constraints.